Determinants of the Exit Ecision of Foreign Banks in India - Swami, Onkar Shivraj; Kumar, N. Arun Vishnu (Ushus Journal of Business Management, 2021)
There is hardly any study in the existing literature regarding the foreign banks’ exit decision in India. This study tries to identify the CAMEL (i.e., C=Capital adequacy, A=Asset quality, M=Management decision, E =Earning ability and L= liquidity) variables that could qualify as the determinant of foreign banks closing their business operations in India which entered after the financial sector reforms. Logistic Regression Model was used to identify the risk factors associated with the closure of business-operation of foreign banks in India.